Razgovor, pogovor kot govorni dogodek - Krajnc Ivič, Mira (Slavistična revija, 2009)
The article tackles a broad area of linguistic and non-linguistic mutual effect and influence in a narrow, select circle of participants, i.e., the area of speecb acts producing a narrow-interest, direct or indirect, one- or two-way dialogue. The focus of the article is the one-way dialogue, called a one-way conversation (Sin. razgovor), and the two-way dialogue, ca1led two-wayconversation (Sin. pogovor).
Keywords: jezikoslovje; leksikologija; lexicology; linguistics; pogovor; razgovor; Slovene; slovenščina